Highly thermostable high molecular-weight low k PIM polymers based on 5, 5′, 6, 6′-tetrahydroxy-3, 3, 3′, 3′-Tetramethylspirobisindane, decafluorobiphenyl, and bisphenols. (16th September 2021) - Konno, Yu; Osuga, Ryota; Kondo, Junko N.; Ye, Rongbin; Tsukamoto, Tadashi; Oishi, Yoshiyuki; Shibasaki, Yuji
Abstract: High-molecular-weight (number average molecular weight M n  = 11–81 kDa) polymers with intrinsic microporosity (PIM) were prepared by the solution polycondensation of 5, 5′, 6, 6′-tetrahydroxy-3, 3, 3′, 3′-tetramethyl-1, 1′-spirobisindane, decafluorobiphenyl, and bisphenols in an aprotic polar solvent at an initial monomer concentration of 0.1 mol/L at 100°C-140 °C for 10–144 h. Transparent (minimum cutoff wavelength of 310 nm), highly thermostable (glass transition temperature of 161°C-376 °C by dynamic mechanical analysis, and 5% weight loss temperature in N2 of 410°C-514 °C) polymer films were fabricated using a solvent-cast method. The copolymer films showed good mechanical properties (tensile strengths of 45–67 MPa, breaking elongation of 2.2%–23.1%, and tensile elastic moduli of 1.5–3.3 GPa) and insulating properties (relative permittivity of 2.27–2.59, and dissipation factor of 0.00191–0.00466 at 20 GHz frequency). The prepared new PIM copolymers are candidates for next-generation low k dielectric materials. Graphical abstract: Image 1 Highlights: Newly designed polymer synthesis protocol containing a PIM skeleton was developed. Polymers showed excellent thermal, mechanical, optical, and insulating properties. Tough and transparent films were obtained.